Information System for Procurement of Goods and Services of the Politeknik Harapan Bersama (SIPHARBER) - Muhamad Bakhar; Evanita Evanita; Ulil Albab (Westscience Press, 2024)
The application of information technology in various fields, including higher education, is rapidly evolving and has extended to critical operational activities such as the procurement of goods and services. This research aims to design and implement a Procurement Information System at Politeknik Harapan Bersama (SIPHARBER), which is expected to enhance efficiency, transparency, and accountability in the procurement process. The system is designed to facilitate coordination between the procurement unit and vendors, reduce the time required for tender processes, and minimize errors in data processing. The development method used for this system is the Waterfall model, which involves stages from requirement analysis to system testing. The outcome of this research is a web-based information system accessible by all related units, enabling real-time monitoring of the procurement process by the leadership, and simplifying vendors' processes to offer their products or services. With the implementation of SIPHARBER, the procurement process at Politeknik Harapan Bersama is expected to be conducted more effectively and efficiently.